Work-related burnout and its associated factors among kindergarten teachers: a multi-center cross-sectional study in Ethiopia - Bezie, Anmut Endalkachew; Zewude, Girum Tareke; Tesfaye, Amensisa Hailu; Yirdaw, Asmare Asrat; Abie, Alebachew Bitew; Abere, Giziew (Frontiers in Public Health, 2025)
IntroductionWork-related burnout is a state of severe physical and mental fatigue and exhaustion resulting from unmanaged prolonged work stress. Kindergarten teachers are at higher risk of work-related burnout compared to other teaching professionals, due to their dual roles as both caregivers and educators for young children. The demands and stresses of these combined responsibilities, coupled with factors such as low salaries, contribute to an increased risk of burnout in this population. Therefore, this study aimed to investigate work-related burnout prevalence and associated factors among kindergarten teachers in Dessie City, Northeast Ethiopia.MethodsAn institution-based, cross-sectional study was conducted in March and April of 2024. A sample of 422 kindergarten teachers was recruited using simple random sampling techniques. A standardized, self-administered Copenhagen Burnout Inventory was utilized to measure work-related burnout. We used EpiData V4.6 and SPSS V26 for data entry and analysis, respectively. A bivariable logistic regression analysis (p-value < 0.2) was performed to find factors associated with work-related burnout. Variables found significant in the bivariable analysis were then exported into a multivariable logistic regression model to identify statistically significant variables at a p value < 0.05 and a 95% confidence interval.ResultsThe response rate was 95% (401/422). 97.5% of the participants were female, and the participants’ mean (standard deviation) age was 28.5 years (SD ± 5.8). In the past 6 months, the total prevalence of WRB was 39.7% [95% CI (34.8, 44.6)]. Work–family conflicts [AOR: 2.81; 95% CI (1.77, 4.45)], working conditions [AOR: 1.63; 95% CI (1.03, 2.56)], perceived stress [AOR: 1.91; 95% CI (1.21, 3.01)], job dissatisfaction [AOR: 1.75, 95% CI (1.10, 2.79)], and kindergarten type [AOR: 1.66; 95% CI (1.02, 2.68)] were factors significantly associated with WRB.ConclusionAccording to this study, a significant number of kindergarten teachers were affected by burnout due to their working nature. To address this issue, interventions focused at reducing work–family conflicts, increasing job satisfaction, and improving the school environment are necessary to support teachers’ well-being, benefiting both young students and the broader educational landscape.